Data: Using a monolithic nickel-based catalyst under steam methane reforming - Shen, Ziqi (Cranfield University, 2023)
This dataset is the experimental data collected from a fixed bed reactor using monolithic catalysts. The reaction related is steam methane reforming (SMR) and tests were performed under different operating temperture, different nickel loading and different gas hourly space velosity (GHSV).
Keywords: 'catalysts'; 'catalysed reaction'; 'Methane reforming'